Analysis of the Use of Audio Media in English Learning for Grade 3 of Wates 02 Elementary School - Cahyaningrum, Aulia Dwi; Damayanti, Mahera Anggi; Asfia, Rizka Dwi; Karini, Vinanda Syafara; Herowati, Desi Indah; Tyas, Dewi Nilam (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the use of audio media in English learning in grade 3 of SD Negeri Wates 02. This study is based on the importance of listening and speaking skills in foreign language learning at elementary school level. The research method used is descriptive qualitative with data collection techniques through questionnaires, observations, interviews, and audio media assessments. The results of the study showed that the majority of students felt interested and motivated by the use of audio media. Audio media was considered appropriate to the subject matter, had good technical quality, and was able to increase active participation and student understanding in learning. However, technical obstacles were found such as a less-than-optimal sound system that affected the clarity of the sound. Overall, audio media has been shown to have a positive impact on students' interest, participation, and learning outcomes in English learning. This study recommends improving the technical quality of audio delivery so that its effectiveness is increasingly optimal in supporting the learning process.